Effusive Elegies or Catty Critic: Letitia Elizabeth Landon On Felicia Hemans - Morrison, Lucy (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractRather than dutifully producing conventional elegies bemoaning the loss of the exemplary woman poet immediately after Felicia Hemans’s death in 1835, Letitia Elizabeth Landon daringly objects to the disjunction between Hemans’s life and her public image. Landon dissents from regarding Hemans’s poetry as unblemished in its depiction of women’s traditional domestic role and instead hints at the subversive, indirect discontent she detects in Hemans’s verse — long before twentieth-century critics. Women writers must surely have enjoyed witnessing their gender’s growing success in the literary market, but, since women were competing against one another directly in the public sphere, it was inevitable that some regarded each other as competitors and experienced envy of others’ achievements. After her sister’s death, Harriet Hughes might record that Hemans “would rejoice in [the gifted writers of her own sex’s] success with true sisterly disinterestedness,” but Landon does not appear to have adopted such a “generous” stance (121).